2013
DOI: 10.1186/1472-6963-13-498
|View full text |Cite
|
Sign up to set email alerts
|

Access to the US Department of Veterans Affairs health system: self-reported barriers to care among returnees of Operations Enduring Freedom and Iraqi Freedom

Abstract: BackgroundThe U.S. Department of Veterans Affairs (VA) implemented the Polytrauma System of Care to meet the health care needs of military and veterans with multiple injuries returning from combat operations in Afghanistan and Iraq. Studies are needed to systematically assess barriers to use of comprehensive and exclusive VA healthcare services from the perspective of veterans with polytrauma and with other complex health outcomes following their service in Afghanistan and Iraq. These perspectives can inform p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…Another glaring problem surrounding seeking initial help and adhering to a program lies in the stigma that surrounds mental health treatment and care. This has been confirmed in study after study -when veterans were asked why they avoided even recommended care, stigma was identified as a major barrier (Currier, Holland, & Allen, 2012;Elnitsky et al, 2013;Koo, 2014). The most important challenges in suicide prevention are stigma surrounding mental illness, negative perceptions of treatment, and other barriers (including confidentiality in the military setting) that result in the majority of service members not accessing care when needed or dropping out prematurely (Held & Owens, 2013).…”
Section: Diagnosed Depression and Predictor Variablesmentioning
confidence: 84%
“…Another glaring problem surrounding seeking initial help and adhering to a program lies in the stigma that surrounds mental health treatment and care. This has been confirmed in study after study -when veterans were asked why they avoided even recommended care, stigma was identified as a major barrier (Currier, Holland, & Allen, 2012;Elnitsky et al, 2013;Koo, 2014). The most important challenges in suicide prevention are stigma surrounding mental illness, negative perceptions of treatment, and other barriers (including confidentiality in the military setting) that result in the majority of service members not accessing care when needed or dropping out prematurely (Held & Owens, 2013).…”
Section: Diagnosed Depression and Predictor Variablesmentioning
confidence: 84%
“…Rather, the challenge is getting veterans to avail themselves of treatment services (Currier, Holland, & Allen, 2012;Elnitsky et al, 2013;Koo & Maguen, 2014). In one post-deployment study, 42% of screened reserve and National Guard soldiers answered questions in such a way that they were flagged as being in need of evaluations and possible treatment (Greden, et al, 2010).…”
mentioning
confidence: 99%
“…Structured clinical interviews were conducted to obtain data on deployment details (e.g., exposure to combat, blasts); pain history; mental health history; current, average, and least pain; emotional symptoms; concussion-related complaints or symptoms; employment status and obstacles; marital or relationship status; satisfaction with VA pain and/or mental health treatment in the last 3 mo (0 = not at all satisfied, 10 = completely satisfied); and perceived barriers to VA medical care and community reintegration (data on self-reported barriers to VA healthcare have been reported previously [26]). This interview was an expansion of one developed in 2005 to identify pain and emotional symptoms in returning combat Veterans.…”
Section: Structured Clinical Interviewsmentioning
confidence: 99%